Business Process Reengineering and the Challenges Facing Airlines, A Critical Study of the Factors Influencing Saudi Airlines' BPR Initiatives - Tayeb, Mamdouh (2005)
Organizations around the globe are being required to become more efficient, responsive, and innovative. In today's quickly changing business environment, companies must organize their work around process. Business Process Reengineering (BPR) has been of great interest to many organizations around the globe, aiming at radical changes and leaps in improvement.